Logistics best practices towards logistics performance in Malaysia moderated with lean logistics - Mohamad Makmor, Mohamad Fared; Jamaluddin, Zaharuzaman; Saad, Mazni (Atlantis Press, 2023)
Malaysia is ranked 41st in the 2018 logistics performance index (LPI)., which ranks the infrastructure and logistical performance of 160 nations. This is a reduction from the ratings of 2014 and 2016, which were 25 and 32, respectively. Singapore, Thailand, and Vietnam are Malaysia's top competitors, and they are ranked 7, 32, and 39 in the LPI 2018 report, respectively. This study explore on how logistics best practices and lean logistics have a moderating impact on logistics performance. 170 logistics companies out of an estimated sample size of 297 form the total population of 1,312 organizations, successfully completed the questionnaires (57.25% response rate). To analyse the data and evaluate the hypotheses, SPSS and PLS-SEM were employed in this study. The findings indicate that management commitment and collaboration had significantly impact the performance while lean logistics does not moderate the relationship between best practices and performance. In Malaysia, this study is a pioneer in the investigation of lean logistics and the use of best practices in logistics to improve logistics performance among SME logistics firms. The limitations of the study were also discussed in this research.